Axial length and associated factors in children: the Shandong Children Eye Study - Lu, Tai Liang; Jonas, Jost B. (Ophthalmologica, 2016)
Purpose: To investigate ocular axial length (AL) in Chinese children. Methods: The Shandong Children Eye Study included 6,364 children aged 4-18 years. Results: Longer AL (mean 23.45 ± 1.20 mm, range 18.80-28.59 mm) was associated (multivariate analysis; correlation coefficient r2: 0.61) with older age (p < 0.001, standardized correlation coefficient β = 0.35, unstandardized regression coefficient B = 0.13, 95% confidence interval [CI] 0.12, 0.15), male gender (p < 0.001, β = -0.24, B = -0.10, 95% CI -0.29, -0.19), urban region (p < 0.001, β = 0.10, B = 0.25, 95% CI 0.20, 0.31), body height (p < 0.001, β = 0.22, B = 0.02, 95% CI 0.01, 0.02), maternal education (p < 0.001, β = 0.07, B = 0.07, 95% CI 0.05, 0.10), paternal myopia (p < 0.001, β = 0.09, B = 0.26, 95% CI 0.20, 0.33), maternal myopia (p < 0.001, β = 0.08, B = 0.23, 95% CI 0.17, 0.30), more time spent indoors reading/writing (p < 0.001, β = 0.05, B = 0.03, 95% CI 0.02, 0.04), less time spent outdoors (p = 0.005, β = -0.03, B = -0.01, 95% CI -0.02, -0.003), longer corneal curvature radius (p < 0.001, β = 0.36, B = 1.63, 95% CI 1.53, 1.74) and higher intraocular pressure (p = 0.008, β = 0.03, B = 0.01, 95% CI 0.004, 0.02). High axial myopia (AL ≥26.0 mm) present in 202 children (3.4 ± 0.2%, 95% CI 2.92, 3.84) was associated with less time spent outdoors (p = 0.002, odds ratio 0.92, 95% CI 0.87, 0.97) in multivariate analysis. Conclusions: In children in the less developed Eastern Chinese province of Shandong, the prevalence of high axial myopia was >10% among 16-year-olds. A modifiable factor associated with higher prevalence of high axial myopia was less time spent outdoors.
Gesehen am 12.02.2019